How Pragmatic Markers Influence Audience Perception in Public Speaking - Bekberganova Khilola; Ilhomov Izzatbek; Bekberganov Avazbek (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Pragmatic markers are regarded as significant linguistic items that are responsible for the interpersonal, textual, and cognitive structuring of oral discourse. In oral presentations, pragmatic markers determine the way audience members receive a speaker's confidence, naturalness, and emotional appeal. The paper discusses the role that pragmatic markers play in shaping audience perception through the presentation speeches of some selected speakers, namely, Barack Obama, Malala Yousafzai, and Steve Jobs. Based on the theory of discourse-pragmatics (Schiffrin, 1987; Fraser, 2009; Aijmer, 2013), the paper explains the way markers, for example, "well," "you know," "I mean," "so," and "actually," determine the audience's perception regarding speaker credibility, fluency, and empathy. The study findings are that pragmatic markers are not filler items but highly strategic linguistic items that promote the increase of coherence, rapport, and persuasion power in the oral presentation situation.